2019
DOI: 10.35913/jk.v6i2.123
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Dukungan Suami Dengan Partisipasi Mengikuti Pemeriksaan Inspeksi Visual Asam Asetat (Iva) Pada Wanita Usia Subur Di Rw 04 Kelurahan Terban Gondokusuman Yogyakarta Tahun 2018

Abstract: Latar Belakang: Indonesia merupakan salah satu negara berkembang di Asia Tenggara yang  menghadapi tantangan bahaya kejadian kanker serviks. kanker serviks memiliki prevalensi tertinggi, yaitu sebesar 0,8%. Salah satu cara deteksi dini kanker seviks adalah dengan pemeriksaan Visual Inspeksi Asam Asetat (VIA). Suami merupakan orang terdekat bagi seorang isteri. Dukungan suami memiliki pengaruh yang signifikan dalam pengambilan keputusan istri, terutama yang berkaitan dengan pencegahan penyakit maupun upaya peni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Jurnal Aisyah: Jurnal Ilmu Kesehatan, 5(2), December 2020, -119 Kartika Adyani;Friska Realita This research is in line with research conducted by Sri and Ratna which concluded that there is a relationship between husband's support and maternal participation in following IVA examinations. (Wahyuni & Adiyasa, 2019). This research is not in line with research conducted by Mitha Ristisuarti which states that there is no relationship between husband's support and IVA examination visits at the Public Health Center of Banguntapan 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Jurnal Aisyah: Jurnal Ilmu Kesehatan, 5(2), December 2020, -119 Kartika Adyani;Friska Realita This research is in line with research conducted by Sri and Ratna which concluded that there is a relationship between husband's support and maternal participation in following IVA examinations. (Wahyuni & Adiyasa, 2019). This research is not in line with research conducted by Mitha Ristisuarti which states that there is no relationship between husband's support and IVA examination visits at the Public Health Center of Banguntapan 2 .…”
Section: Resultsmentioning
confidence: 99%
“…One can gain access to information through electronic media, printed media, the internet, etc. 22 To maximize access to information received by WRA, in addition to print and electronic media, information can also be obtained most effectively through counselling. Counselling can be administered formally (through socialization) or informally (through social gatherings and women's religious groups, for example).…”
Section: Discussionmentioning
confidence: 99%
“…Dukungan dari orang lain atau kelompok terdekat memiliki pengaruh signifikan terhadap perilaku seseorang dalam hal kesehatan. Apabila seseorang memiliki lingkaran sosial yang memahami kesehatan dengan baik, hal tersebut akan mempengaruhi pola hidup wanita tersebut (Wahyuni & Adiyasa, 2019). Prevalensi kanker serviks di Indonesia menempati peringkat kedua tertinggi dengan 23.4 kasus per 100.000 wanita dan tingkat kematian mencapai 13.9 per 100.000 wanita.…”
Section: Pendahuluanunclassified